Study on the Variation Rule and Characteristics of Pore Water Pressure in the Failure Process of Saturated Rock - Yuezheng Zhang (Shock and Vibration)
With the development of tunnels and other engineering constructions into the deep strata, rock masses are more prone to dynamic damage such as rock bursts under in situ conditions and excavation disturbances. The pore water in the rock mass will produce pressure changes during this process. According to the relationship between the change of pore water pressure and the development of rock mass damage, the variation rule and precursor characteristics of pore water pressure in the process of rock mass failure can be found. In this paper, through mechanical analysis, the evolution law of pore water pressure during the failure process of saturated rock is obtained. The study found that, in the process of rock failure, the pore water pressure presents three stages of linear growth, transition, and decrease. The rise and fall of pore water pressure are closely related to rock damage and influence each other. Through the observation of pore water pressure during coal mining, it is found that the coseismic effect of pore water pressure is significant. It is proved that there is a close correlation between the evolution of the stress field in the surrounding area of the stope and the change of pore water pressure in the surrounding area under the effect of mining disturbance. During the engineering practice, dynamic monitoring can be carried out on the change of pore water pressure inside the rock mass according to the law, and the precursor information of rock mass instability and failure can be explored.